Community tourism and its role among agropastoralists in Laikipia County, Kenya. Issue 1 (February 2017) - Owuor, George; Knerr, Beatrice; Ochieng, Justus; Wambua, Tom; Magero, Chris
The authors present survey findings from agropastoral households living near tourist attraction sites and undertake agropastoral activities, conservation, and community tourism enterprises in Laikipia, Kenya. Laikipia is a major wildlife migration route, popular with private conservancies and ranches, attracting large numbers of tourists. The authors explore the key determinants of participation in community tourism and find that communication and road infrastructure, membership of community groups, and security aspects influence household participation in community tourism. Policies aiming to improve infrastructure and security and to encourage the formation of investment groups would enhance participation in community tourism activities and raise household incomes.